التوافق النفسي الاجتماعي و الشذوذ الجنسي لدى الشباب البطال - بجة, حياة; بليردوح, كوكب الزمان (جامعة الوادي - University of Eloued, 2021)
ملخص : تهدف الدراسة الحالية لتحديد مستوى التوافق النفسي الاجتماعي و قياس مدى إنتشار السمة العامة للشذوذ الجنسي في أوساط الشباب البطال لولاية باتنة بالإضافة إلى وصف العلاقة بين كل من التوافق النفسي الاجتماعي و الشذوذ الجنسي لدى ذات العينة ، تم الإعتماد على المنهج الوصفي الإرتباطي باستخدام مقياسي : التوافق النفسي الاجتماعي لزينب شقير 2003 و مقياس معدل الانحرافات الجنسية لأشرف محمد أحمد علي 2017 على عينة مكونة من 30 شاب بطال (بمعدل 9 إناث و 21 ذكور) المقيمين داخل حدود ولاية باتنة ، و كانت النتائج كالتالي: - مستوى التوافق النفسي الاجتماعي منخفض لدى الشباب البطال. - هناك إرتفاع في مستوى السمة العامة للشذوذ الجنسي لدى الشباب البطال. - هناك علاقة إرتباطية عكسية بين التوافق النفسي الاجتماعي و سمة الشذوذ الجنسي لدى الشباب البطال. Abstract: The present study aims to determine the level of psychosocial compatibility and measuring the prevalence of the general characteristic of sexual deviation among the unemployed youth of the governorate of Batna, in addition to describing the relationship between psychosocial compatibility and sexual deviation in the same sample. Zainab Choucair 2003 and Ashraf Muhammad Ahmad Ali's Sexual Deviation Rate Scale 2017 were used on a sample of unemployed youth (30 males with an average of 9 females and 21 males) residing within the borders of Batna wilaya, and the results were as follows: -The level of psychosocial compatibility is low among unemployed youth. - An increase in the general characteristic of sexual deviation among unemployed youth. - There is a reversible correlation between psychosocial compatibility and sexual deviation among the unemployed youth.
دراسة ميدانية على مستوى ولاية باتنة
مقال
Keywords: شذوذ جنسي ; توافق نفسي اجتماعي ; شباب بطال; sexual deviation؛ psychosocial compatibility؛ unemployed youth